In the blink of an eye: understanding teachers' relational competence from a micro-sociological perspective. Issue 1 (2nd January 2023) - Aspelin, Jonas; Eklöf, Anders
ABSTRACT: A substantial body of international research argues that the teacher-student relationship is crucial for students' academic and social-emotional learning. However, microanalytic studies of teachers' relational competence are rare. This article aims to contribute such a study by exploring teachers' relational competence, drawing on Erving Goffman's concept of face-work and focussing on how a particular teacher-student relationship is constructed in an ongoing processes of interaction. The paper presents in-depth analyses of teacher-student interaction using a video-recording of a classroom episode. In the episode, the student loses face as a result of a complex series of events. The teacher, through rapid action, helps the student repair face and manages to (re-)establish a respectful interaction ritual. Overall, the teacher's relational competence is manifested by advanced and complex face-work. Our analyses indicate that relational competence is essentially a micro-social artistry – a lightning-quick ability to interact with students in the 'here and now'. The article also discusses the pedagogical implications of these findings, for example, that it is crucial to include face-work in teacher education and training.